Are flexible working hours helpful in stabilizing unemployment? - Marcin Kolasa; Michał Rubaszek; Małgorzata Walerych (Bank of Finland, 2019)
In this paper we challenge the conventional view that increasing working time exibility limits the amplitude of unemployment fluctuations. We start by showing that hours per worker in European countries are much less procyclical than in the US, and in some economies even co-move negatively with output. This is confirmed by the results from a structural VAR model for the euro area, in which working hours increase after a contractionary monetary shock, exacerbating the upward pressure on unemployment. To understand these counterintuitive results, we develop a structural search and matching macroeconomic model with endogenous job separation. We show that this feature is key to generate countercyclical adjustments in working hours. When we augment the model with frictions in working hours adjustment and estimate it using euro area time series, we find that increasing flexibility of working time amplifies cyclical movements in unemployment.
URN:NBN:fi:bof-201910031516
Keywords: E24; E32; J22; J64; 330